Association of adult weight gain and nonalcoholic fatty liver in a cross-sectional study in Wan Song Community, China - Zhang,W.-J. (2014)
Our objective was to examine associations of adult weight gain and nonalcoholic fatty liver disease (NAFLD). Cross-sectional interview data from 844 residents in Wan Song Community from October 2009 to April 2010 were analyzed in multivariate logistic regression models to examine odds ratios (OR) and 95% confidence intervals (CI) between NAFLD and weight change from age 20. Questionnaires, physical examinations, laboratory examinations, and ultrasonographic examination of the liver were carried out. Maximum rate of weight gain, body mass index, waist circumference, waist-to-hip ratio, systolic blood pressure, diastolic blood pressure, fasting blood glucose, cholesterol, triglycerides, uric acid, and alanine transaminase were higher in the NAFLD group than in the control group. HDL-C in the NAFLD group was lower than in the control group. As weight gain increased (measured as the difference between current weight and weight at age 20 years), the OR of NAFLD increased in multivariate models. NAFLD OR rose with increasing weight gain as follows: OR (95%CI) for NAFLD associated with weight gain of 20+ kg compared to stable weight (change <5 kg) was 4.23 (2.49-7.09). Significantly increased NAFLD OR were observed even for weight gains of 5-9.9 kg. For the “age 20 to highest lifetime weight” metric, the OR of NAFLD also increased as weight gain increased. For the “age 20 to highest lifetime weight” metric and the “age 20 to current weight” metric, insulin resistance index (HOMA-IR) increased as weight gain increased (P<0.001). In a stepwise multivariate regression analysis, significant association was observed between adult weight gain and NAFLD (OR=1.027, 95%CI=1.002-1.055, P=0.025). We conclude that adult weight gain is strongly associated with NAFLD.